2012
DOI: 10.1063/1.4757984
|View full text |Cite
|
Sign up to set email alerts
|

Generation of extreme state of water by spherical wire array underwater electrical explosion

Abstract: The results of the first experiments on the underwater electrical explosion of a spherical wire array generating a converging strong shock wave are reported. Using a moderate pulse power generator with a stored energy of ≤6 kJ and discharge current of ≤500 kA with a rise-time of ∼300 ns, explosions of Cu and Al wire arrays of different diameters and with a different number and diameter of wires were tested. Electrical, optical, and destruction diagnostics were used to determine the energy deposited into the ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
16
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 19 publications
1
16
1
Order By: Relevance
“…This value of d w can be calculated using the known value of the pressure at that location obtained from the results of hydro-dynamic simultions 25 and the EOS of water 31,32 P w À P 0w ¼ 3 Â 10 8 ½d 7:15 À 1, which is valid up to 2 Â 10 10 Pa, where P w and P 0w are the pressure behind the SW front and normal pressure, respectively. The results of HD simulations showed that at radius r ¼ 1.5 mm, the value of the SW pressure on the water-copper boundary wall reaches $1.2 Â 10 10 Pa.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This value of d w can be calculated using the known value of the pressure at that location obtained from the results of hydro-dynamic simultions 25 and the EOS of water 31,32 P w À P 0w ¼ 3 Â 10 8 ½d 7:15 À 1, which is valid up to 2 Â 10 10 Pa, where P w and P 0w are the pressure behind the SW front and normal pressure, respectively. The results of HD simulations showed that at radius r ¼ 1.5 mm, the value of the SW pressure on the water-copper boundary wall reaches $1.2 Â 10 10 Pa.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the spherical implosion of an SW allows one to obtain a ðr=r 0 Þ 0:66 larger pressure than does a cylindrical SW implosion for the same initial values of p 0 and r 0 . Indeed, experimental studies of the underwater electrical explosion of a spherical wire array 25,26 and numerical one-dimension HD simulations showed that in the vicinity of the implosion origin (r % 3 lm), one can expect to obtain in water P $ 6 Â 10 12 Pa, T $ 30 eV, and q $ 10 g/cm 3 . In these experiments, also the TOF of the SW to the origin of the implosion was measured.…”
mentioning
confidence: 99%
“…A significant increase in the parameters of water was achieved in experiments with a sub-microsecond (sub-ls) timescale explosion of a spherical wire array. 15 In this research, the experimental and numerical simulation results indicate that the convergence of the spherical SSW leads to the formation of an extreme state of water in the vicinity (r ¼ 5 lm) of the implosion origin that is characterized by pressure, temperature, and density of 2000 GPa, 8 eV, and 7 g/cm 3 , respectively.…”
mentioning
confidence: 67%
“…In this letter, we present the experimental results of underwater electrical explosion of a spherical wire array using a rather simple microsecond (ls) timescale ($1.1 ls) generator 11 and a comparison of these results with those obtained in a study that was similar but in which a sub-ls ($350 ns) timescale high-current generator was used. 15 When a ls timescale generator is used, one can expect that the SSW generated by the explosion of the wire array will propagate for a longer distance under the applied external forces caused by the explosion. The latter could lead to a larger energy being delivered to the vicinity of the implosion origin, due to the smaller energy losses of the SSW during its implosion.…”
mentioning
confidence: 99%
“…Indeed, only the last few tens of microns of spherical SW propagation in the vicinity of the converging origin were obtained by detecting intense light emission from that location, and these data were used as the TOF for comparison with the results of the 1D-HD simulations. 12,20 In the present experiments, we studied the dynamics of the convergence of the spherical SW using measurements of the change in the intensity of the CW laser beam (k ¼ 532 nm, 30 mW) guided by a lens to the input of the optical fiber. The fiber has a core diameter of 0.2 mm and it was covered by a non-transparent thin (0.25 lm) dielectric tube.…”
Section: Experimental Setup and Resultsmentioning
confidence: 99%